Nefritis Lupus: Klasifikasi dan Tata Laksana Terkini: Tinjauan Pustaka - Irianto; Willy Sunjaya; Jonathan Koswara (Cermin Dunia Kedokteran, 2025)
Lupus nephritis (LN) is one of the most common complications in systemic lupus erythematosus. If not detected quickly, LN will often cause reduced kidney function in five years necessitating kidney replacement. Diagnosis and classification of LN are made with a kidney biopsy. The drug of choice is based on the histopathology classification and needs to be tailored case by case. If complete remission is not achieved or if it relapses, the causes need to be investigated. More nephron cells can be saved in earlier therapy to prevent end stage kidney disease complications.